2004
DOI: 10.1103/physrevb.69.245401
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent surface luminescence in ZnO nanowires

Abstract: Nanometer sized whiskers ͑nanowires͒ offer a vehicle for the study of size-dependent phenomena. While quantum-size effects are commonly expected and easily predicted, size reduction also causes more atoms to be closer to the surface. Here we show that intensity relations of below-band-gap and band-edge luminescence in ZnO nanowires depend on the wire radius. Assuming a surface layer wherein the surface-recombination probability is 1 ͑surface-recombination approximation͒, we explain this size effect in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
493
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(544 citation statements)
references
References 31 publications
42
493
9
Order By: Relevance
“…Recently, Shalish et al [23] demonstrated that this luminescence arise form the surface of the ZnO while Norberg and Gamelin established it is directly correlated with the surface hydroxide concentration [24]. Thus, the study of this emission is a suitable tool to investigate the modification in the surface dependence of the PL visible emission with the type of capping molecule is in agreement with the surface origin [23,24], as the molecules can alter only the electronic structure close to the surface.…”
Section: /11mentioning
confidence: 87%
“…Recently, Shalish et al [23] demonstrated that this luminescence arise form the surface of the ZnO while Norberg and Gamelin established it is directly correlated with the surface hydroxide concentration [24]. Thus, the study of this emission is a suitable tool to investigate the modification in the surface dependence of the PL visible emission with the type of capping molecule is in agreement with the surface origin [23,24], as the molecules can alter only the electronic structure close to the surface.…”
Section: /11mentioning
confidence: 87%
“…The weak luminescence centered at ∼380 nm has been attributed to excitonic recombination. 5,6,9,11,14,18 The broad sub-bandgap emission in the PL and EL spectra is believed to be due to defects and surface states. 5,6,11,18 The spectral characteristics are reproducible across different devices, and all three devices exhibit an enhancement of the short wavelength emission with increasing bias voltage.…”
mentioning
confidence: 99%
“…The visible luminescence of ZnO nanocrystals located around 510-520 nm (''green'' emission) is affected by the surface (Matsumoto et al, 2002;Norberg & Gamelin, 2005;Ramakrishna & Ghosh, 2003;Shalish et al 2004;VanDijken et al, 2000a;Van Dijken et al, 2001). A direct relationship between the size and the excitonic emission intensity in ZnO crystals in the 40-2500 nm size range was reported (Matsumoto et al, 2002;Shalish et al 2004;Van Dijken et al, 2001). Moreover the ''green'' emission intensity was reported to display a direct correlation with surface hydroxide concentrations (Liu et al, 1992;Norberg & Gamelin, 2005;Van Dijken et al, 2000b).…”
Section: Zno Nanocrystals Capped By Rh6gmentioning
confidence: 90%
“…Improvement of the (NBE/VB) intensity ratio indicates that dangling bonds and defect states in the surface layer of ZnO nanocrystals are significantly passivated by dye. The visible luminescence of ZnO nanocrystals located around 510-520 nm (''green'' emission) is affected by the surface (Matsumoto et al, 2002;Norberg & Gamelin, 2005;Ramakrishna & Ghosh, 2003;Shalish et al 2004;VanDijken et al, 2000a;Van Dijken et al, 2001). A direct relationship between the size and the excitonic emission intensity in ZnO crystals in the 40-2500 nm size range was reported (Matsumoto et al, 2002;Shalish et al 2004;Van Dijken et al, 2001).…”
Section: Zno Nanocrystals Capped By Rh6gmentioning
confidence: 99%